Microbiological and Physicochemical Quality of Groundwater and Risk Factors for Its Pollution in Ouagadougou, Burkina Faso - Traoré Oumar; Kpoda Dissinviel Stéphane; Dembélé René; Saba Courage Kosi Setsoafia; Cairns Johannes; Barro Nicolas; Haukka Kaisa (MDPI, 2025)
Ouagadougou is a city with three million inhabitants and an increasing demand for water of sufficient quality. New boreholes are drilled to match demand, but their protection from anthropogenic contamination is insufficient. To assess the quality of urban groundwater in Ouagadougou for the first time, a total of 32 borehole water samples were collected and assessed for bacteriological and physicochemical features using established methods. Health risk inspections and hazard assessments were undertaken at sampling sites to identify potential hazards and contributing factors. Statistical analysis was used to identify associations between risk factors and water pollution. The study revealed poor quality of groundwater in Ouagadougou with major nonconformities related to total coliforms, Escherichia coli, and turbidity. Water samples from 19 boreholes (59%) were contaminated with coliforms, and 11 (34%) with E. coli. Additionally, Pseudomonas aeruginosa, Enterococcus, and anaerobic sulphite-reducing bacterial spores were detected. Deviations from physicochemical quality requirements were observed for water turbidity, pH, nitrate, fluorine, and iron. Risk analysis showed the major high-risk practices to be sludge spreading or having a garbage heap, a latrine, a septic tank, or dirty water near a borehole. Based on these results, for public health protection, authorities must take strict measures to prohibit such practices around these important sources of drinking water in Ouagadougou.